Animal Models and "Omics" Technologies for Identification of Novel Biomarkers and Drug Targets to Prevent Heart Failure. (7th July 2015) - Hou, Yunlong; Adrian-Segarra, Juan M.; Richter, Manfred; Kubin, Natalia; Shin, Jaeyoung; Werner, Isabella; Walther, Thomas; Schönburg, Markus; Pöling, Jochen; Warnecke, Henning; Braun, Thomas; Kostin, Sawa; et al.
Abstract : It is now accepted that heart failure (HF) is a complex multifunctional disease rather than simply a hemodynamic dysfunction. Despite its complexity, stressed cardiomyocytes often follow conserved patterns of structural remodelling in order to adapt, survive, and regenerate. When cardiac adaptations cannot cope with mechanical, ischemic, and metabolic loads efficiently or become chronically activated, as, for example, after infection, then the ongoing structural remodelling and dedifferentiation often lead to compromised pump function and patient death. It is, therefore, of major importance to understand key events in the progression from a compensatory left ventricular (LV) systolic dysfunction to a decompensatory LV systolic dysfunction and HF. To achieve this, various animal models in combination with an "omics" toolbox can be used. These approaches will ultimately lead to the identification of an arsenal of biomarkers and therapeutic targets which have the potential to shape the medicine of the future.